2006
DOI: 10.1149/1.2201253
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Device to Measure Electrode Response to Changes in Electrolyte Composition

Abstract: A microfluidic device is used to measure electrode response to rapid changes in electrolyte composition. These changes in composition are achieved by switching the electrolyte flowing through an electrolyte channel containing a working and counter electrode. In the present investigation, the time response of the device was characterized by reducing tri-iodide ions at a rate controlled by mass-transfer to the electrode surface. Results are compared with finite-element simulations that assume an ideal two-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…30,31 This cell was originally designed to resolve fast electrolyte changes over the working electrode. However in this work we used it to minimize ohmic resistance, while simultaneously controlling working electrode hydrodynamics.…”
Section: Methodsmentioning
confidence: 99%
“…30,31 This cell was originally designed to resolve fast electrolyte changes over the working electrode. However in this work we used it to minimize ohmic resistance, while simultaneously controlling working electrode hydrodynamics.…”
Section: Methodsmentioning
confidence: 99%
“…The channel design for the cell has been discussed in detail elsewhere. 24 Briefly, the microfluidic channels were molded from polydimethylsiloxane ͑PDMS͒ over a negative pattern created from SU-8 photolithography. The working channel had a rectangular cross section 500 m wide and 180 m tall, as confirmed by profilometry, through which the plating solution was flowed at 30 mL/h or 9.3 cm/s.…”
Section: Methodsmentioning
confidence: 99%
“…24,27 Figure 4a shows galvanostatic plating at −6.6 mA/cm 2 with 300 ppm of the indicated suppressor molecule introduced at time t = 0, either alone ͑solid lines͒ or with 10 ppm SPS ͑dashed lines͒. The additives were removed at time t = 108 s, when the plating bath returned to VMS.…”
Section: D148mentioning
confidence: 99%
“…To emulate the latter condition, a microfluidic device was used to observe in-situ changes on the electrode structure: the electrolyte flow is a medium to induce shear stress on the electrode surface. [10][11][12] This shear stress was correlated with the shear stress observed on the electrode surface during the flexing of the battery. Learning from these studies, we demonstrated a flexible battery electrode based on a mesh embedded architecture.…”
mentioning
confidence: 82%